Государство и эволюция: [16+] / Егор Гайдар - Гайдар Егор Тимурович (Центр книги Рудомино, 2014)
Экземпляры: СФ (201406) / Инвентарный номер: 50019 / Цена: 280.00 / Сис.шифр: 66.3 (2Рос) / Авт.знак: Г 14 / ГРНТИ: 11 / ББК: 66.3 (2Рос)